Usage issues of SSL/TLS issues - Бабенко, Тетяна Василівна; Толюпа, Сергій Васильович; Гречко, Вікторія Володимирівна (Ukrainian Information Security Research Journal, 2017)
One of the means of creating a secure communication ses-sion is using the SSL/TLS cryptographic protocol, how-ever it does not guarantee full protection and also has its own vulnerabilities and disadvantages, which must be ana-lyzed and eliminated in the future. In particular, in this pa-per the basic terminology is analyzed, vulnerabilities of the protocol are analyzed and generalized, some aspects that make possible implementation of the “man in the middle” attack and it’s variations,the problem of certificates substi-tution and self-signed certificates, authentication defects, application libraries vulnerabilities, key exchange problem, including the Bleichenbacher’s threat, public key infra-structure problems, the problem of interoperability in Ukraine and the most recent vulnerabilities of this protocol are presented (SWEET32, DROWN, ROBOT). The result of the research is the arranged list of unsolved problems and recommendations to increase cryptoresistability level of the protocol.